Impact of planting density on biomass and carbon stock of short rotation tree species under high density conditions - Satyawali, Kavita; Chaturvedi, Sumit; Bisht, Neema; Maikhuri, Seema; Tewari, Salil; Kaushal, Rajesh (Indian Journal of Agroforestry, 2020)
The biomass and carbon accumulation in different above and belowground components of six years old Eucalyptus camaldulensis and Melia azedarach planted at four spacings were evaluated in Tarai region of central Himalaya. The total biomass (330.7 t ha-1) and carbon stock (160.4 t ha-1) were recorded to be higher in E. camaldulensis. As the spacing increased, individual stems increased in diameter and total biomass; however, total biomass production per hectare decreased. Biomass allocation in aboveground components followed the order: bole>branch>twig>leaves, whereas, in belowground components: stump root, lateral root, fine root, in Eucalyptus and Melia, respectively. Maximum total tree biomass (286.0 t ha-1) and total carbon storage (131.2 t ha-1) was observed in 3 m × 1 m, followed by 3 m × 2 m, 3 m × 2.5 m and 3 m × 1.5 m. Mean carbon concentration in all the aboveground components of both species varied from 40-50%. However, soil carbon stock was found higher (61.54 t ha-1) under M. azedarach which decreased with soil depth. Among the different spacing, maximum soil carbon stock was accumulated in 3 m × 1 m spacing which decreased with each successive increase in spacing. Thus, the study indicated superiority of E. camaldulensis over M. azedarach for biomass production and carbon accumulation at dense spacing, whereas, soil carbon stock was found to be greater under M. azedarach.